2022
DOI: 10.1371/journal.pone.0273849
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the intention to adopt wearable payment devices in China: The use of hybrid SEM-Neural network approach

Abstract: Wearable payment devices (WPD) are gaining acceptance fast and transforming everyday life and commercial operations in China. Limited research works were conducted on customers’ adoption intentions to obtain a real image of the evolution of WPD in China. This study aims to investigate the effects of Performance Expectancy (PE), Effort Expectancy (EE), Social Influence (SI), Facilitating Conditions (FC), Hedonic Motivation (HM), Perceived Trust (PT), and Lifestyle Compatibility (LC) on the intention to adopt WP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The level of trust between the two parties is an essential component that has a direct and significant bearing on the desire to make a transaction. Several studies, including those conducted by Kim et al, 53 Luyao et al, 54 and Nawi et al, 16 have shown that customers’ trust beliefs have a favorable impact on their intention to make an online purchase. Understanding the importance of these factors can enhance their relationships with consumers and create more opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…The level of trust between the two parties is an essential component that has a direct and significant bearing on the desire to make a transaction. Several studies, including those conducted by Kim et al, 53 Luyao et al, 54 and Nawi et al, 16 have shown that customers’ trust beliefs have a favorable impact on their intention to make an online purchase. Understanding the importance of these factors can enhance their relationships with consumers and create more opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…Effort expectancy (EE) is defined as the perception of the degree of ease associated with using a system or technology [47]. Numerous empirical studies have proven that effort expectancy is found to influence behavioral intention [26,57]. Adjei et al (2021) found a positive relationship between effort expectancy and the intention to use mobile phone-based Interactive Voice Response in a rural area of Ghana [58].…”
Section: Effort Expectancymentioning
confidence: 99%
“…Venkatesh et al define the facilitating conditions construct as the extent to which an individual believes that the organizational and technical infrastructure exists to support system use (Zhai et al, 2021). In the Luyao literature, Lin et al stated that facilitating conditions are the availability and adequacy of better and more profitable resources, lower financial costs, and a higher level of service-providing support, making it possible to make contactless payments such as mobile payments (Luyao et al, 2022).…”
Section: Facilitating Conditionmentioning
confidence: 99%